Public Relations Communication in Building Parents' Trust in Islamic Education Institutions - Andrianto Andrianto; Agus Fawaid; Suheri (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2026)
This study aims to analyze the role of public relations communication in building parental trust in Islamic educational institutions, especially in the Abu Zairi Salafiyah Islamic Boarding School. Using qualitative approaches and case study methods, this study collects data through interviews, observations, and documentation. The results show that communication that is open, transparent, and involves various information channels, such as regular meetings, social media, and internal newspapers, has a significant impact on increasing parental trust. Parents feel more involved in their children's educational process, which strengthens emotional connections and supports the achievement of educational goals. This research contributes to the development of educational communication theory, especially in the context of Islamic educational institutions, and suggests the importance of a holistic communication approach in building and maintaining parental trust in Islamic boarding schools. However, this study is limited to one institution, so further research with a wider sample is needed.